Implementation of the Scaffolding Approach in Teaching Popular Scientific Article Writing to Eighth-Grade Students at MTsN 2 Bungo - Zulfa Fitri Aini; Agus Setyonegoro; Priyanto Priyanto; Andiopenta Purba (Asosiasi Dosen Muda Indonesia, 2026)
Writing is a complex language skill because it requires mastery of structure, idea development, and accurate linguistic rules. In the context of the Independent Curriculum, the ability to write popular scientific articles is crucial for strengthening the literacy of junior high school (SMP/MTs) students. However, classroom learning practices still show low structural regularity and idea development due to minimal gradual guidance. This study aims to describe the implementation of the scaffolding approach in teaching popular scientific articles to eighth-grade students at MTsN 2 Bungo and identify supporting and inhibiting factors. This study used a qualitative research type with an instrumental case study design. Data were obtained through learning observations, document analysis of 32 student articles, and interviews with teachers and students. Then, they were analyzed descriptively through stages of reduction, categorization, and thematic interpretation with triangulation of sources and techniques. The results showed that scaffolding was implemented gradually through providing intensive assistance in the initial stage, simplifying tasks, providing examples and feedback, and reducing assistance (fading). Most students were able to structure texts in a more organized manner, develop ideas logically, and show improvements in linguistic aspects and writing independence. It was concluded that the scaffolding approach effectively improves the quality of the writing process and products while encouraging students' learning independence, and is relevant to the learning principles in the Independent Curriculum.